Comparative structural analysis of dairy sub regions pampeanas (Veterinary Science, 2017)
The dairy region of La Pampa is divided into three subregions (north, center and south) with different agro-ecological and technological features. These differences warrant a detailed study to differentiate the characteristics of their production systems. The aim of this study was to compare each other's holdings of the three Pampeanassubregions analyzing structural features in order to get a detailed report of the situation to detect strengths and weaknesses, differences and similarities that allow to implement further actions to improve the primary provincial diary sector in an effective and selective way. It was used a stratified random sampling design in districts with proportional allocation, according to the methodology proposed by FAO (Food and Agriculture Organization). The information was collected in 2011 through 56 surveys carried out directly to the producers. 37 variables were analyzed and it was concluded that the Central subregion is the one with the largest diversification into other productions such as agriculture. There is great difference in the size of the farms within each subarea. The central and southern subregions have low stocking rate.The pastoral base of food plus the supplementation of concentrates, pasture rolls and corn silage identify semipastoriles systems prevailing in the Pampeana regions (80%), however the degree of intensification in grazing management and supplements opens a big variety of possibilities with dairy farms that are closer to the stabled and others to the purely pastoral.
Keywords: Structure; Dairy subregions